Hydrogen and oxygen fuel enrichment effects on a HD diesel engine - Monemian, Emad; Cairns, Alasdair; Pedrozo, V. (Iranian Society of Engine, 2017)
Implementing emission regulations in the transport sector is enforcing manufacturers to improve performance of Heavy Duty (HD) vehicles as they are accountable for 25% of CO2 emissions within EU. The currently reported research was involved with evaluating partial replacement of hydrogen with diesel fuel experimentally and intake air enrichment with oxygen in a heavy-duty diesel single cylinder engine. Fumigation of hydrogen was done into the intake system at two particular engine loads (6 and 12 bar IMEPn). Indicated efficiency was increased up to 4.6% at 6 bar IMEPn and 2.4% at 12 bar IMEPn, while reducing CO2 emissions by 58% and 32% at 6 and 12 bar IMEPn respectively. Applying diesel pre-injection was required in order to mitigate the high pressure rise rates known as combustion noise. Furthermore, intake air enrichment with oxygen resulted in faster combustion process. This could curb soot and minimised CO emissions to the detriment of NOx increase.